Analysis of shielding effectiveness in different kinds of electromagnetic shielding fabrics under different test conditions. Issue 3 (February 2019) - Li, Yaping; Wang, Xiuchen; Pan, Zhen; Su, Ying; Liu, Zhe; Duan, Jiajia; Li, Yayun
This study used the DR-SO4 window method to test the shielding effectiveness of silver-plated fiber functional fabric, copper–nickel duplicate coating fabric, and stainless steel fiber-blended-type fabric. These electromagnetic shielding fabrics exhibited different levels of shielding effectiveness under different polarization directions. In the same frequency, the shielding effectiveness difference between the vertical polarization wave direction and horizontal or 45° polarization wave direction is higher in silver-plated fiber functional fabric and copper–nickel duplicate coating fabric than that in stainless steel fiber-blended fabric. The radiation distance of 1.5 m has great influence on the shielding effectiveness of the three fabrics. These fabrics show a repeated and intersected change in wrinkle degrees of 1# and 2#. The fabrics in the wrinkle degree of 2# have higher shielding effectiveness than that of 3#. The wrinkle recovery properties of electromagnetic shielding fabrics also affect their shielding effectiveness. The shielding effectiveness of copper–nickel duplicate coating fabric with low wrinkle recovery property considerably changes. This research provides a basis for the design of electromagnetic shielding fabrics.